Behavioral resurgence in individuals varying in depression, anxiety, and autism-associated tendencies - Phil Reed (Heliyon, 2019)
Resurgence is the reappearance of a previously reinforced, but then extinguished behavior, when an alternative behavior that has been reinforced to replace it is also extinguished. This phenomenon has been suggested as important in the re-occurrence of many clinical problems, but little is known currently about the relationship between this process and different psychopathological traits. This experiment addressed this gap by comparing the levels of resurgent behavior in participants scoring lower or higher on depression-, anxiety-, and autism-related characteristics. Sixty participants completed an experimental task of three phases. In the first, they were presented with a concurrent RR-5 ext schedule, in the second with a conc ext RR-5 schedule (each lasting 6min), and finally with a conc ext ext schedule (lasting 2 min). Following this, all participants completed the Beck Depression Inventory, State-Trait Anxiety Inventory, and Autism Quotient, questionnaires provided. Participants showed a resurgence of responding at test from the response extinguished in Phase 2 that was greater for those with lower levels of depression, but high levels of anxiety. These findings are discussed in terms of their implications for understanding individual differences in terms of psychiatric symptomatology, for their treatment, and in terms of theoretical predictions derived for the various psychopathologies.